Causes of Inflation in Turkey: A Literature Survey with Special Reference to Theories of Inflation - Aykut Kibritçioğlu (Inflation and Disinflation in Turkey, 2002)
Turkey has experienced high and persistent inflation for more than twenty years. This chapter attempts firstly to survey the extremely broad literature on theories of inflation, in order to be able to classify, understand and discuss the dynamics of inflation more carefully. In this chapter, it is mainly argued that inflation may be interpreted as a net result of sophisticated and continuous interactions of demand-side (or monetary) shocks, supply-side (or real) shocks, price-adjustment (or inertial) factors and political processes (or institutional factors). The second aim of the chapter is to compare the existing empirical studies on Turkish inflation, by considering their sample period, data frequency, empirical methods, modeled macroeconomic variables and main results. Most of the studies reviewed here seem to have focused primarily on demand-side determinants (e. g., monetary growth and budget deficits), and partially on some supply-side factors (e. g., nominal exchange rates and oil prices). On the other hand, the components, degree and effects of inflation inertia need to be investigated in more detail. In the future, the modeling attempts of the inflationary dynamics in Turkey would profit from the so-called “new political macroeconomics” because the role of the political process and institutions is not a weak explanatory factor of Turkish inflation that is easily ignored.
Keywords: B22; E31; 330; Inflation theories; Turkey; causes of inflation; political economy of inflation